Adolescents’ Responses to Marital Conflict: The Role of Cooperative Marital Conflict - Zhou, Nan (J Fam Psychol, 2017)
Not all youth exposed to hostile marital interactions develop negative responses to marital conflict. Cooperative marital conflict has long been considered as an important way of managing conflict and may serve as an important context in which hostility might convey during marital interactions. In light of little prior attention placed on the positive side of conflict processes, the main and moderating effects of cooperative marital conflict on youth responses to marital conflict were examined in a sample of 416 two-parent families using a multi-method, two-year prospective design. Cooperative marital conflict was associated with decreases in youth emotional dysregulation, perceived threat, and behavioral dysregulation, and increases in constructive family representations and coping efficacy. As a specific dimension of cooperation, effective conflict resolution was associated uniquely with elevated youth coping efficacy, and decreased emotional and behavioral dysregulation; marital warmth was associated uniquely with increased constructive family representations. Significant interactions between marital hostility and marital cooperation also were found. These findings highlight the importance of examining cooperation above and beyond hostility in studies of marital conflict in order to better understand youth development during early adolescence.